Contribution of Good Governance Principles to Strengthening Zakat Management in Indonesia: Confirmatory Factor Analysis - Hani Tahliani (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Good governance is a crucial issue in strengthening the performance of zakat institutions. This research aims to elaborate good governance from the perspective of Islam and analyze the factors contributing to good corporate governance in a number of zakat institutions in Indonesia. Confirmatory Factor Analysis (CFA) is employed to measure the contribution of each indicator to the five principles of good governance in zakat institutions, namely transparency, accountability, responsibility, independence, and fairness. With the assistance of Partial Least Squares (PLS) version 3 it is shown that the principle of transparency contributes 60.4%; the principle of accountability 4.82%; the principle of responsibility 6.41%; and the principle of independence 53.3%. Therefore, it can be concluded that good governance in zakat institutions has been well implemented in some aspects but has not yet been implemented comprehensively. This research is significant in that it contributes guidelines on zakat management, provides teaching materials for higher education, and serves as a reference for the formulation of policies and regulations related to the standardization of good governance in zakat institutions.